Diagnostic accuracy of computed tomography to identify adenomas among adrenal incidentalomas in an endocrinological population. Issue 5 (May 2018) - Marty, M; Gaye, D; Perez, P; Auder, C; Nunes, M L; Ferriere, A; Haissaguerre, M; Tabarin, A
Abstract : Context: The recent recommendations of the European Endocrine Society states that the performance of computed tomography (CT) to characterize 'true' adrenal incidentalomas (AIs) remains debatable. Objective: To determine relevant thresholds for usual CT parameters for the diagnosis of benign tumors using robust reference standard among a large series of 'true' AIs recruited in an endocrinological setting. Design: Retrospective study of 253 AIs in 233 consecutive patients explored in a single university hospital: 183 adenomas, 33 pheochromocytomas, 23 adrenocortical carcinomas, 5 other malignant tumors and 9 other benign tumors. Reference standard was histopathology in 118 AIs, biological diagnosis of pheochromocytoma in 2 AIs and size stability after at least 1 year of follow-up in 133 AIs. Methods: Sensitivity, specificity and positive and negative predictive values were estimated for various thresholds of size, unenhanced attenuation (UA), relative and absolute wash-out (RPW, APW) of contrast media. 197 scans were reviewed independently in a blinded fashion by two expert radiologists to assess inter-observer reproducibility of measurements. Results: Criteria associated with a 100% positive predictive value for the diagnosis of benign AI were: a combination of size and UA: 30 mm and 20 HU or 40 mm and 15 HU, respectively; RPW >53%; and APW >78%. Non-adenomatous AIs with rapid contrast wash-out were exclusively benign pseudocysts and pheochromocytomas, suggesting that classical thresholds of 60% and 40% for APW and RPW, respectively, can be safely used for patients with normal metanephrine values. Inter-observer reproducibility of all parameters was excellent (intra-class correlation coefficients: 0.96–0.99). Conclusions: Our study, the largest conducted in AIs recruited in an endocrinological setting, suggests safe thresholds for quantitative CT parameters to avoid false diagnoses of benignity.